ASSESSMENT OF COMPANY’S BUSINESS REPUTATION - Kasimova Sayora Karimjon qizi (Journals Park Publishing, 2023)
Today among top-level managers, there is an increasing need to take into account and evaluate assets that do not have a tangible form, but can bring benefits to the company like material assets do. That’s why it is obvious that non-property assets can also significantly affect the company’s value, the growth of the value of securities and the level of investor confidence. The goodwill of the company is its intangible asset, it can have a significant impact on sustainability and favorable development of the company if it is properly managed. In the article we use comprehensive analysis tools, namely, compilation, system, statistical, critical and analytical approaches. Integrated approach to assessing business reputation is the result of the study. The value of the article in practical application is the use of the approach to assessing business reputation in order to increase the value of the enterprise as a whole in a number of individual cases.
Keywords: business reputation, goodwill, company value, assessment.